La Cuba secreta: la insularidad / cubanidad en Cristina García - Pietrak, Mariola (Romanica Silesiana)
The article aims to analyze the literary work of the Cuban‑American novelist Cristina García from the viewpoint of the theory of insularity, proposed by her countrymate J. Lezama Lima («Coloquio con Juan Ramón Jiménez», 1938), paying attention to the references to the enchanted / sacred space evoked in the esseistic work of María Zambrano (“La Cuba secreta”, 1948). Starting with these two fundamental notions, it aims to deal with the very idea of cubanity in the writings of the so‑called Generation 1’5, to whom Zambrano belongs. As the author was born in Cuba, but raised in the United States, her perception of the island is necessarily ambiguous, typical for the sensibility of Cuban exiles, of those people who find themselves in a land between, living between two cultures. Key words: insularity, cubanity, Generation 1’5, Cuban diaspora